2019
DOI: 10.1159/000502635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Muscle Fitness in Dialysis Patients: A Systematic Review and Meta-Analysis

Abstract: Background: Lack of exercise is a prevalent problem in patients receiving dialysis. Although guidelines recommend these patients to undertake suitable exercise, no exercise type or intensity has been suggested, and the effect of exercise on muscle fitness in dialysis patients is not clear. This study investigated the effect of exercise on muscle fitness, including muscle mass, muscle strength, and physical performance, in patients on dialysis. Methods: A systematic review and a meta-analysis of randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Therefore, the reduction in BMI that was found was mostly accompanied by an increase in MAMC which means a preservation of muscle mass, with a relevant reduction in FM. These results are in concordance with studies including measurements of muscle mass by BIA and the calculation of SMI in which muscle mass as well as SMI increased after resistance exercise and were found to have a tendency to increase in the aerobic training group [ 46 , 69 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the reduction in BMI that was found was mostly accompanied by an increase in MAMC which means a preservation of muscle mass, with a relevant reduction in FM. These results are in concordance with studies including measurements of muscle mass by BIA and the calculation of SMI in which muscle mass as well as SMI increased after resistance exercise and were found to have a tendency to increase in the aerobic training group [ 46 , 69 ].…”
Section: Discussionsupporting
confidence: 90%
“…In previous systematic reviews, the beneficial effects of exercise on the physical health of patients undergoing HD [ 33 , 34 , 35 , 36 , 37 , 38 ] as well as on the QoL were illuminated [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In two studies by Lu et al [ 46 ] and Molsted et al [ 47 ], the positive effects of exercise on muscle mass and muscle strength in patients undergoing HD were also stressed out. Nevertheless, according to our knowledge, there are no published studies in which the total body composition and nutritional status of patients undergoing HD in relation to exercise have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous systematic reviews and meta-analysis have examined the effects of exercise in general within the HD population 49,51,53,55,56 . Moreover, the most recent meta-analysis showed the most beneficial effects of combined (strength and aerobic) exercise in HD patients 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that a walking intervention not only prevented decline in muscle mass but also resulted in a slight increase. Prior studies of moderate or vigorous resistance exercise training in dialysis patients have shown significant improvements in muscle mass [19,22,23], and it may be that more vigorous exercise training results in greater increase in muscle mass [39]. However, only a fraction of dialysis patients are able to participate in such interventions [40].…”
Section: Discussionmentioning
confidence: 99%